THE MODERATING EFFECT OF QUALIFICATION IN THE NEXUS VALUE STREAM MAPPING AND PRODUCTIVITY IMPROVEMENT (American Journal of Interdisciplinary Research and Development, 2023)
This study aims at finding out the impact of the value stream mapping strategy and investing it as a technique to improve productivity, which enables the organization to achieve a competitive position that will bring it success and sustainability. To achieve the purpose of the study, a questionnaire was adopted. The sample of the study involved 137 employees from different departments of Al- Diwaniyah Tires Factory. According to the purpose of the study, a main hypothesis was formulated, A set of statistical methods were used through the statistical program (Spss vr.24) and (AMOS vr.24) programs. It is hoped that this study will be of value in a step to enrich thought in an attempt to identify the reality and level of application of the value stream mapping as a strategy to improve the performance of the organization and attempt to draw attention to the need to adopt a value stream mapping as an influential factor in productivity improvement. In addition, this research explore the moderating variables that can affect this relationship. Several conclusions have been come up with Including: the existence of a significant direct effect of the value stream mapping in the productivity improvement and qualification as a moderating variable in the relationship.